Impact of preoperative malnutrition, based on albumin level and body mass index, on operative outcomes in noncirrhosis patients with colorectal liver metastasis - Guo, Yixian; Wang, Yufeng; Liu, Runkun; Li, Hanqi; Yin, Guozhi; Tuo, Hang; Zhu, Yifeng; Wang, Yiheng; Yang, Wei; Liu, Zhikui (Frontiers in Surgery, 2025)
BackgroundSerum albumin level and body mass index (BMI), acting as indicators of nutritional status, are commonly applied to predict surgical outcomes in cancer patients. This study aimed to evaluate the impact of preoperative serum albumin level and BMI on the operative outcomes of noncirrhotic patients with colorectal cancer liver metastasis who underwent hepatectomy.MethodsThis was a retrospective study of medical records from the period between January 2013 and December 2022. Preoperative malnutrition was defined as hypoalbuminemia with a serum albumin level of <35 g/L before surgery or a BMI of <18.5 kg/m2 within 30 days before surgery. Multiple statistical methods were applied to analyze the data, including the two-independent sample t-test, analysis of variance, Chi-squared test, and multivariate analysis.ResultsAmong the 159 eligible patients, 42 (26.4%) were classified into the preoperative malnutrition group. The incidence of blood transfusion (45.24% vs. 18.80%, P = 0.040) was significantly higher in the malnutrition group. The drainage volume was significantly higher on the first day [65 (115) vs. 60 (80), P < 0.05] and the second day [50 (95) vs. 40 (79) P < 0.05] in the malnutrition group than that in the nonmalnutrition group. Postoperative hemoglobin levels were significantly lower in the malnutrition group (101.20 ± 2.43 vs. 108.76 ± 1.61, P = 0.015). Therefore, the incidence of grade Ⅱ or Ⅲ/Ⅳ complications was significantly higher in the malnutrition group (16.67% vs. 5.31% or 11.9% vs. 3.42%, P = 0.001), and the length of hospital stay was significantly extended [18 (12) vs. 15 (8), P = 0.002]. In the multivariate analysis, preoperative malnutrition [odds ratio (OR) = 5.548, 95% CI 1.508–20.413, p = 0.010] and operation time (OR = 1.009, 95% CI 1.002–1.016, P = 0.0011) were identified as independent predictors of postoperative complications.ConclusionPreoperative malnutrition in patients who underwent hepatectomy for colorectal cancer liver metastasis was associated with worse surgical outcomes, especially aggrandizing the emergence of postoperative complications.